Clavicle fractures. (2nd July 2020) - Morgan, Catrin; Bennett-Brown, Katharine; Stebbings, Alexandra; Li, Lily; Dattani, Rupen
Abstract : Clavicle fractures account for approximately 2–5% of all fractures in adults and 10–15% in children. There is a bimodal distribution, with two peaks occurring in patients <25 years of age as a result of direct trauma and in those >55 years of age secondary to a fall onto an outstretched arm. Approximately two-thirds of all clavicle fractures occur in men. This article provides an overview of the presentation, assessment and management of clavicle fractures for both core surgical trainees and acute care common stem/emergency medicine trainees.